IoT based Smart Passenger Surveillance System for Airport - P.Deepa, T.; Pradeepa.P, Dr (International Journal of Engineering and Technology, 2018)
Airport security system is mandatory in all developing and developed countries. The major threat to any countryâ€™s economy, health and development is targeted and transported via airports which are evident from the past historical examples. The developments in Science and Technology have improved the methods of surveillance but failed to address few key health issues including privacy. The main objective of this paper is to develop a smart IOT based surveillance systems that is implemented in airport in smart screening without causing any unpleasant disturbances to the passengers. This paper makes use of the recently developed smart sensors, Tiva processor from Texas instruments connected via IOT and cloud and a remote station to effectively secure the airport area and overcoming all the real time challenges.Â